Ethical Generational Marketing Approach for Dental Patients - Sergi, V; Liakopoulou, E; Fotou, F; Leonidou, V; Prountzos, G; Antoniadou, Maria (British Journal of Healthcare and Medical Research, 2023)
Dental marketing is one of the most challenging fields of marketing in the health field, due to the combination of dentistry science and business administration. Dentists, despite their medical occupation, are the leaders of their business and to succeed, they should use ethical marketing strategies avoiding patient’s deception. This narrative review analyses the current possible marketing strategies by identifying and exploiting existing opportunities; it also aims to demonstrate new approaches in dental marketing, which can be used to cope with the effects of the economic crisis, inflation, and after-Covid-19 market’s competition. In addition, it mentions the marketing techniques and the ways to approach every specific generation of dental patients to get maximum results. Generational marketing is not considered a complete strategy, but it’s relevant for marketers to understand their costumer’s perspectives. At the stage of planning, dentists should take into consideration the characteristics of the target generation and integrate the relevant method of approach into their marketing strategy. According to the generation features, there are specific techniques of ethical and legal approach, that can be included in marketing strategy to maximize efficiency. Moreover, dentists should never debase those characteristics, such as honesty and integrity, which are considered indisputable by people across all generations.